The Spirit in Baptism and the Lord’s Supper: An Exegesis of 1Corinthians 12:13 - Ádám SZABADOS (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
This exegetical study on 1Corinthians 12:13 argues that, despite the tendency of late 20th c. Anglo-Saxon evangelical scholarship to use the verse as an interpretive key to understand the “Spirit-baptism” of the Gospels and Acts, the earlier view, which saw water-baptism and the Lord’s supper in the verse, is still plausible. The paper examines the larger literary context of the epistle and the immediate literary context of the verse and concludes that both make the theme of unity the interpretive grid of the apostle’s sentence. A comparison with 1Corinthians 10:1–4 further confirms the central role of baptism and the Lord’s Supper as a theme of unity in Paul’s mind. Linguistic considerations also demonstrate that there is no compelling reason to question the Spirit’s agency in the verse. The main conclusion of the paper is that in 1Corinthians 12:13 Paul is speaking about baptism and the Lord’s Supper as well-known signs of Christian unity. This unity is created under the influence of the Holy Spirit, the influence behind baptism, and is expressed every time Christians eat the spiritual food and drink the spiritual drink of the Lord’s supper.